In silico Screening of Myristicin, Elemicin, Isoelemicin and Malalabaricone C for their activity towards obesity related enzyme 17β-hydroxysteroid dehydrogenase (1BHS) - Rosy Mallik (International Journal of Modern Agriculture, 2020)
Screening of some of the compounds found in nutmeg extract Myristicin, Elemicin, Isoelemicin and Malalabaricone C against a protein target 1BHS associated with type 2 diabetes mellitus have been carried out and discussed in the current study. The 3D structures of the ligands and the protein were obtained from PubChem database and Protein Data Bank respectively. Each ligand was prepared and docked against the target protein using AutoDock Vina. Activity of each compounds towards the obesity related protein 1BHS was predicted. Among the four phytochemicals, highest binding affinity and most number of hydrogen bonding were observed for Malalabaricone C